Komunikasi Ritual Tradisi Megat Sabuk di Pura Kemaliq Lingsar - Ratna Anjani; Ida Bagus Made Arjana (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research aims to examine ritual communication in the Megat Sabuk tradition in Lombok. Megat Sabuk tradition is one of the unique cultural heritage that is still preserved by the people in Lombok. This research uses a qualitative approach to ethnographic methods, a qualitative approach with ethnographic methods can enable researchers to explore and understand the phenomenon of the Megat Sabuk tradition ritual based on the point of view of the Megat Sabuk tradition actors. Data collection techniques are obtained through interviews, participatory observation, and documentation. The results of this study indicate that the meaning of the Megat Sabuk tradition means a tradition passed down from ancestors as a form of devotion and respect for ancestors who have preceded which must be carried out continuously for a harmonious life, the impact that occurs if the tradition is not carried out is that unexpected things will occur such as health problems in offspring and family, and the form of communication in the Megat Sabuk tradition ritual, the form of communication that occurs in this tradition is interpersonal communication. This type of communication in this tradition uses verbal and nonverbal communication.